Level of contamination of milk with HCH and DDT in Haryana - KUMAR, BEENA; KATHPAL, T S (The Indian Journal of Animal Sciences, 2013)
Bovine milk samples (24) were collected periodically from September 1991 to February 1992 from The Hisar District Co-operative Milk Producer’s Union Ltd for knowing their contamination with DDT and HCH residues. Analysis of samples by GLC-ECD revealed 100% contamination with HCH residues. Total HCH residues varied from 0.009-0.179 alphag ml-1, Among all HCH-isomers gamma was present in minimum amounts whereas beta-isomer dominated varying from 0.001-0.063 betag ml-1. DDT wee present in 12 out of 24 samples. Total DDT and P,P-DDE. The rice straw and husk samples (15 each) analysed for HCH contamination showed 100% contamination. Rice straw contained average residue to a level of 0.080-0.322 alphag g-1 whereas in rice husk total HCH residue varied from 0.088-0.447 alphag g-1. Consumption of contaminated rice straw and other animal feed by milch animals are the possible causes of contamination of milk.